The Effect of School Principal Supervision on Teacher Professionalism in SMA Pekanbaru - Isjoni Isjoni; Sumardi Sumardi; Daeng Ayub Natuna (International Journal of Educational Best Practices, 2017)
There are a number of the phenomenon among high school teachers in Pekanbaru. Some of them are in low spirit of work in performing tasks, fewer rewards for teachers, lack of teaching preparation, lack of attention from school principals in running the school vision and mission, low performance of the deputy principal, and absence of regular supervision of the principal. Based on the above description, this paper is aimed at investigating the following research question: Does the principal supervision affect the professionalism of high school teachers in Pekanbaru?. The population of this quantitative research type is 137 people. 104 people were selected as the sample using proportional random sampling. Data were collected through distributing a questionnaire to the respondents after testing its validity and reliability. This study revealed that there is a positive influence of principal supervision (X) on teacher professionalism (Y) in SMA Pekanbaru. This means that the better and more effective the principal supervision (X), then, the higher the teacher professionalism (Y) will be. Therefore, Principal Supervision (X) is an important variable for improving Teacher Professionalism (Y).